GASTRONOMIC TOURISM STUDY OF DJEJAK RASA AS A TOURIST ATTRACTION IN THE CULINARY EXPLORATION IN YOGYAKARTA - Dewi, Roels Ni Made Sri Puspa; Yovanca, Elzishilla Aline; Utami, Nisa Rahmaniyah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Djejak Rasa is a business built to introduce Yogyakarta culinary tourism from a gastronomic perspective. This business is a place to get to know more about Yogyakarta specialties. Therefore the purpose of this research was to study Djejak Rasa in introducing culinary tourism to tourists. Djejak Rasa has programs that have been implemented so far, namely Kelana Rasa, Ruang Rasa, and Curation Rasa. The research method used is descriptive qualitative research. Methods of data collection through participant observation, interviews, and documentation. The informant determination technique used purposive sampling. The number of informants, namely all managers and tourists who did gastronomic tours with Djejak Rasa, totaled 18 people. The method of data analysis is assisted by the process and stages of observation which consist of selection, recording, a series of behaviors and situations as well as empirical objectives. These stages are carried out until the data is fulfilled and the data analysis process is complete. The result of this research is that tourists can get to know more about cuisine and the stories contained therein. One of the Kota Gede Taste Search programs is one of the intensive tours conducted by Djejak Rasa. This trip takes approximately 4 to 5 hours. At least seven tourist attractions were visited, namely the Mataram Coffee Barn, the Waru Flower Production House, Legi Kota Gede Market, the Gede Mosque Area, and the King's Tomb of Mataram and Between the Two Gates. Every place visited provides educational tours, both historical tours and cultural gastronomy tours. Gastronomic tourism such as to learn about the names of food, its ingredients, how to process it, how to serve it, the properties and benefits of food as well as its stories and philosophy.